Clinical and radiographic peri‐implant parameters and proinflammatory cytokine levels among cigarette smokers, smokeless tobacco users, and nontobacco users. (15th December 2017) - Akram, Zohaib; Vohra, Fahim; Bukhari, Ishfaq A.; Sheikh, Saeed A.; Javed, Fawad
Abstract: Background: It is postulated that clinical and radiographic peri‐implant parameters are worse and levels of interleukin (IL)‐1β and matrix metalloproteinase (MMP)‐9 in the peri‐implant sulcular fluid (PISF) are higher in cigarette‐smokers (CS) and smokeless‐tobacco users (STU) compared with nontobacco user (NTU). Purpose: The present study aimed to compare clinical and radiographic peri‐implant inflammatory parameters and levels of IL‐1β and MMP‐9 levels among CS, STU, and NTU. Materials and Methods: Forty‐five CS (Group‐1), 42 STU (Group‐2), and 44 NTU (Group‐3) were included. Demographic data was collected using a structured baseline questionnaire. Peri‐implant plaque index (PI), bleeding on probing (BOP), and probing depth (PD) were recorded and crestal bone loss (CBL) were assessed using standardized digital radiographs. PISF volume and levels of IL‐1β and MMP‐9 in PISF were quantified using enzyme‐linked immunosorbent assay. Clinical peri‐implant parameters and PISF IL‐1β and MMP‐9 concentrations were analyzed with Kruskal‐Wallis test. Bonferroni post hoc adjustment test was used for multiple comparisons. P ‐value was set at .05. Results: Peri‐implant PI and PD were significantly worse in group‐1 and group‐2 patients as compared to group‐3 individuals ( P < .05). Peri‐implant CBL was also significantly higher in group‐1 and group‐2 compared with group‐3 ( P < .05). Peri‐implant BOP was significantly higher in group‐2 and group‐3 as compared to group‐1 individuals ( P < .05). The PISF volume ( P < .05) collected and levels of IL‐1β and MMP‐9 were statistically significantly elevated among individuals in group‐1 and group‐2 compared with group‐3 ( P < .01). There was no significant difference in PI, PD, CBL, and PISF levels of IL‐1β and MMP‐9 among participants in groups 1 and 2. Conclusion: Clinical and radiographic peri‐implant parameters were compromised among CS and STU as compared to NTU. Increased expression of local proinflammatory cytokines may explain greater susceptibility of CS and STU to peri‐implant breakdown.